Information and Communications Technology in the Education Sector in India - Nirupam Bajpai; John Biberman; Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
India has successfully achieved quantity benchmarks for education by making schooling accessible to all and making rapid strides in improving attendance. Next, India must improve the quality of its educational system, which is limited by large class sizes, limited teacher expertise, poor access to resources, and teacher absenteeism. ICT provides tools to address all these challenges. Historically, ICT has been used to improve educational coverage. Educational radio programs have been produced since 1972, and corporate initiatives have introduced computers to classrooms since the 1990s. Most radically, India even launched a satellite to broadcast educational content to remote schools off the grid. Yet the digital revolution provides the greatest opportunity for ICT to contribute to improved education and equality of opportunity across India. ICT has been applied to improve education in several ways. Teachers can gain access to improved lesson plans and teaching resources that incorporate multimedia and best pedagogical practices. Similarly, these platforms are used to deliver interactive teacher training that uses data to analyze teachers' strengths and weaknesses. Data can also be used to break down and isolate challenges for students or entire classrooms. Finally, communication tools embedded in these platforms provide teachers, students and parents with a more collaborative classroom experience. (...)
Keywords: 330